2020
DOI: 10.1556/2006.2020.00023
|View full text |Cite
|
Sign up to set email alerts
|

Comparing generalized and specific problematic smartphone/internet use: Longitudinal relationships between smartphone application-based addiction and social media addiction and psychological distress

Abstract: Background and aimsThe literature has proposed two types of problematic smartphone/internet use: generalized problematic use and specific problematic use. However, longitudinal findings on the associations between the two types of problematic use and psychological distress are lacking among East-Asians. The present study examined temporal associations between both generalized and specific problematic use of the smartphone/internet, and psychological distress.MethodsHong Kong University students (N = 308; 100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
93
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 135 publications
(116 citation statements)
references
References 34 publications
(61 reference statements)
7
93
1
1
Order By: Relevance
“…PSU and PSMU among children have been of concern to clinicians and policy makers because of their purported association with children's psychological health, although the model of compensatory internet use suggests a continuum for smartphone and social media use (i.e., from non-problematic to problematic) (15). Indeed, several studies have suggested that PSU and PSMU are associated with greater depression, anxiety, and stress (16)(17)(18)(19)(20)(21). The social distancing and school suspensions due to COVID-19 could possibly lead to undesirable lifestyle changes.…”
Section: Introductionmentioning
confidence: 99%
“…PSU and PSMU among children have been of concern to clinicians and policy makers because of their purported association with children's psychological health, although the model of compensatory internet use suggests a continuum for smartphone and social media use (i.e., from non-problematic to problematic) (15). Indeed, several studies have suggested that PSU and PSMU are associated with greater depression, anxiety, and stress (16)(17)(18)(19)(20)(21). The social distancing and school suspensions due to COVID-19 could possibly lead to undesirable lifestyle changes.…”
Section: Introductionmentioning
confidence: 99%
“…The term "problematic smartphone use" was used in a recent study of smartphone use types of psychiatric symptoms. According to a recent study by Chen et al, problematic smartphone use can be divided into two categories in the field of Internet addiction: general problematic smartphone use and specific problematic smartphone use (8)(9)(10). General problematic smartphone use indicates general behavioral patterns of excessive smartphone use, which may have negative consequences to the individuals (11).…”
Section: Introductionmentioning
confidence: 99%
“…These very popular and attractive sites are designed to keep users engaged and for many individuals their use can be habitual and/or excessive taking time away from activities that may be more important such as educational and/or occupational duties. Consequently, excessive social media use, like other types of excessive use such as excessive internet or smartphone use, may cause a variety of health problems, including sleep problems, musculoskeletal discomfort, mood issues and impaired daily functions, as well as addiction‐like consequences in a small minority of individuals 27‐36 …”
Section: Introductionmentioning
confidence: 99%